Pengaruh Model Pembelajaran Berbasis Proyek (PBP) Terhadap Hasil Belajar pada Materi Menulis Teks Editorial - Irsan Vanni; Desi Sukenti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The learning model affects student learning outcomes seen from the ability of students who do not understand the material to write editorial texts because the teacher uses the conventional model. Researchers are interested in examining learning outcomes using a project-based learning model. (PBP). The problems studied were (1) "Is there any influence of the Project-Based Learning (PBP) model on learning outcomes in editorial text material for class XII students of SMAN 9 Pekanbaru"? (2) "Is the Project-Based Learning (PBP) model superior to the conventional learning model for learning outcomes in editorial text material for class XII students at SMAN 9 Pekanbaru"? This research was conducted at SMAN 9 Pekanbaru. Quasi-experimental research methods. The research sample was 37 students of class XII IPA 1 (experimental class) and 37 students of class IPA 2 (control class). The instrument is in the form of a test and is tested using the "One Sample t-test" from the results of the calculation of the sig value. (2-tailed) of 0.013 <0.05. It can be concluded that the results of the post-test have a positive effect which is shown on the average learning outcomes of the experimental class is better than the control class. table tcount < ttable (2.61 <2.13) By stating that the Project Based Learning (PBP) model is superior to learning outcomes in Indonesian language editorial text writing material.